Makna tradisi Nyadhar dalam penguatan identitas nasional masyarakat Sumenep - Afifah, Wildani (Maliki Interdisciplinary Journal, 2026)
Indonesia is known as a country with extraordinary cultural richness. Each region in Indonesia has its own traditions, customs, languages, and local wisdom that shape the identity of its people. In Sumenep Regency, the Nyadhar tradition is still preserved by the community to this day. The Nyadhar tradition is a ritual performed by salt farmers as a form of gratitude to God and respect for their ancestors, who played a significant role in the development of salt ponds. This study aims to examine the meaning of the Nyadhar tradition and its role in strengthening the community’s national identity. The results will demonstrate that the Nyadhar traditions contains religious, social, historical, cultural, and economic values that are curcial for maintaining community unity and passing on local culture. These values contribute to the formation of national identity, as local culture is a key element in building the character of the Indonesian nation. Therefore, the Nyadhar tradition is not only important for the people of Sumenep but also for the community of the national cultural identity.